Activation of peroxymonosulfate by carbonaceous oxygen groups: Experimental and density functional theory calculations - Wang, Y.; Ao, Z.; Sun, Hongqi; Duan, X.; Wang, Shaobin (Elsevier BV, 2016)
© 2016 Elsevier B.V. The active sites for metal-free carbocatalysis in environmental remediation are intricate compared to those for traditional metal-based catalysis. In this study, we report a facile fabrication of amorphous carbon spheres with varying oxygen functional groups by hydrothermal treatment of glucose solutions. With air/N2 annealing and regeneration in the glucose solution of the as-synthesized carbon spheres, the concentrations of oxygen-containing groups were tailored on the amorphous carbon spheres in an Excess-On-Off-On manner. Accordingly, an Off-On-Off-On catalytic behavior in peroxymonosulfate (PMS) activation using these amorphous carbon spheres was observed. To uncover the mechanism of catalytic activity, electron spin resonance (EPR) spectra were recorded to investigate the variation of the generated OH and SO4-radicals. Moreover, density functional theory (DFT) studies were employed to identify the role of oxygen-containing groups on the amorphous carbon spheres in adsorptive OO bond activation of PMS. Results revealed that ketone groups (CO) are the dominant active sites for PMS activation among oxygen-containing functional groups. In order to simulate real wastewater treatment, influences of chloride anions and humic acid on PMS activation for phenol degradation were further evaluated. This study provides an in-depth insight to discovering the role of oxygen-containing functional groups as the active sites in metal-free carbocatalysis.